The Affect of Tax Awareness, Tax Service, and Tax Penalty on The Tax Compliance (A Case Study on the District’s Treasurer in Garut Regency) - Khariidatul Bahiyyah; Rita Yuniarti (Jurnal Wacana Ekonomi, 2023)
The purpose of this study is to testing the affect of tax awareness, tax service, and tax penalty on the tax compliance of the district’s treasurer in Garut Regency. The type of this research was quantitative with descriptive analysis research method. The samples in this research used probability sampling technique with cluster sampling, and it resulted in the total samples of 59 the district’s treasurer who were also taxpayers. The hypothesis testing was conducted through t-test. The result obtained from this research showed that the tax awareness and tax penalty influenced the tax compliance, while the tax service did not affect the tax compliance.